Effects of late-season sheep grazing following intensive-early steer grazing on population dynamics of sericea lespedeza (lespedeza cuneata) - Lemmon, Jack Edward William (Kansas State University, 2021)
Mature ewes were used in a 2-yr experiment to evaluate effects of intensive late-season grazing with sheep on vigor of sericea lespedeza (Lespedeza cuneata; hereafter sericea) in native tallgrass prairie. Pastures (n = 8; 31 ± 3.6 ha) infested with sericea (initial basal frequency = 1.4 ± 0.81%) were assigned randomly to 1 of 2 treatments: early-season grazing with beef steers (1.1 ha/steer; initial BW = 258 ± 1.7 kg) from 15 April to 15 July followed by 60 d of rest (control; STR) or steer grazing from 15 April to 15 July followed by intensive grazing with mature ewes (0.2 ha/ewe; SHP) from 1 August to 1 October. Ewes (initial BW = 65 ± 3.1 kg) were assigned randomly to graze 4 of 8 pastures; remaining pastures were not grazed from 1 August to 1 October. Vegetation responses to treatment were measured along 4 permanent 100-m transects in each pasture. Herbivory of sericea was monitored weekly in each pasture from 21 July to 7 October. Herbivory of sericea in SHP and STR on 21 July was not different (P = 0.51). Herbivory of individual sericea plants was greater (P < 0.01) in SHP than in STR by the end of wk 1 of the sheep-grazing period (10.6 vs. 0.5%); moreover, herbivory of sericea lespedeza steadily increased (P ≤ 0.01) such that 92.1% of sericea lespedeza plants had been grazed in SHP compared to 1.4% in STR by wk 8 of the sheep-grazing period. Whole-plant DM weight of sericea lespedeza at dormancy was less (P < 0.01) in SHP than in STR. Additionally, annual seed production by sericea lespedeza was less (P < 0.01) in SHP than in STR (114 vs. 864 seeds/plant). Pasture forage biomass was not different (P = 0.76) between SHP and STR after the steer-grazing period on 21 July. Conversely, STR had more (P < 0.01) residual forage biomass than SHP at the end of the sheep-grazing period (i.e., on 7 October). Growth performance of beef steers grazing from 15 April to 15 July annually was not different (P ≥ 0.59) between treatments. Our results were interpreted to suggest that intensive late-season grazing by sheep decreased vigor of sericea lespedeza but did not affect growth performance of grazing steers. Although late-season sheep grazing decreased residual forage biomass by 904 kg DM/ha compared with late-season rest, residual biomass was likely adequate to prevent soil-moisture loss and erosion during the dormant season and was sufficient to allow prescribed fire application in the following spring seasons.
Keywords: Biological weed control; Grazing; Lespedeza cuneata; Sheep; Tallgrass prairie